Ghosts and religious life in early China - Pu, Muzhou 1952- (Cambridge University Press, 2022)
For modern people, ghost stories are no more than thrilling entertainment. For those living in antiquity, ghosts were far more serious beings, as they could affect the life and death of people and cause endless fear and anxiety. How did ancient societies imagine what ghosts looked like, what they could do, and how people could deal with them? From the vantage point of modernity, what can we learn about an obscure, but no less important aspect of an ancient culture? In this volume, Mu-chou Poo explores the ghosts of ancient China, the ideas that they nurtured, and their role in its culture. His study provides fascinating insights into the interaction between the idea of ghosts and religious activities, literary imagination, and social life devoted to them. Comparing Chinese ghosts with those of ancient Egypt, Mesopotamia, Greece, and Rome, Poo also offers a wider perspective on the role of ghosts in human history
Title from publisher's bibliographic system (viewed on 13 Jan 2022)
Ghost : the other side of humanity -- The emergence of ghosts in early China -- Imperial order and local variations -- Stories that reveal the dark corner -- Ghosts in early Daoist religious culture -- The taming of ghosts in early Buddhism -- Chinese ghosts in a comparative perspective
Keywords: Geschichte Anfänge-500; Ghosts / China / History; Geisterglaube; China / Religion / History; China